Pengembangan Model Evaluasi Sumatif Mata Pelajaran PAI di Sekolah Dasar - Magdalena, Ina; Kumarani, Nanda Citra (ANWARUL, 2023)
Evaluation is a process of making a decision based on the results of an assessment. Evaluation will always be in the teaching and learning process. Summative evaluation is a form of assessment that is commonly known and used by teachers in schools. Evaluation will always be used in the school environment, both SD, SMP, and SMA/SMK to find out and assess the progress of students. Summative evaluation is a type of evaluation used to determine student achievement at the end of learning. Summative evaluation at the elementary and secondary education levels aims to assess the achievement of learning objectives and/or Learning Outcomes (CP) of students, as a basis for determining grade increases and/or graduation from educational units. To find out the learning outcomes of students in learning Islamic religious education, the teacher must have knowledge about the evaluation of learning outcomes, including the methods and steps for evaluating learning outcomes, so that the completed evaluation can be measured.